(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article requirements of creating texts of communication in pupils` books of secondary schools. Mainly, this need can be met as a result of the formation of skills to create a communicative text in a consistent manner in the learning process. To do this, it is important to focus the content of learning tasks, exercises, didactic processes in the learning process on the formation of the student’s ability to create a communicative text.